Effectiveness of appropriately trained nurses in preoperative assessment: randomised controlled equivalence/non-inferiority trial. Issue 7376 (7th December 2002) - Kinley, Helen; Czoski-Murray, Carolyn; George, Steve; McCabe, Chris; Primrose, John; Reilly, Charles; Wood, Richard; Nicolson, Paula; Healy, Caroline; Read, Susan; Norman, John; Janke, Ellen; et al.
Abstract: Objective: To determine whether preoperative assessments carried out by appropriately trained nurses are inferior in quality to those carried out by preregistration house officers. Design : Randomised controlled equivalence/non-inferiority trial. Setting : Four NHS hospitals in three trusts. Three of the four were teaching hospitals. Participants : All patients attending for assessment before general anaesthesia for general, vascular, urological, or breast surgery between April 1998 and March 1999. Intervention : Assessment by one of three appropriately trained nurses or by one of several preregistration house officers. Main outcome measures : History taken, physical examination, and investigations ordered. Measures evaluated by a specialist registrar in anaesthetics and placed in four categories: correct, overassessment, underassessment not affecting management, and underassessment possibly affecting management (primary outcome). Results : 1907 patients were randomised, and 1874 completed the study; 926 were assessed by house officers and 948 by nurses. Overall 121/948 (13%) assessments carried out by nurses were judged to have possibly affected management compared with 138/926 (15%) of those performed by house officers. Nurses were judged to be non-inferior to house officers in assessment, although there was variation among them in terms of the quality of history taking. The house officers ordered considerably more unnecessary tests than the nurses (218/926 (24%) v 129/948 (14%). Conclusions : There is no reason to inhibit the development of nurse led preoperative assessment provided that the nurses involved receive adequate training. However, house officers will continue to require experience in preoperative assessment.